2020
DOI: 10.1080/19490976.2020.1785252
|View full text |Cite
|
Sign up to set email alerts
|

The gut microbiome stability is altered by probiotic ingestion and improved by the continuous supplementation of galactooligosaccharide

Abstract: The stable gut microbiome plays a key role in sustaining host health, while the instability of gut microbiome also has been found to be a risk factor of various metabolic diseases. At the ecological and evolutionary scales, the inevitable competition between the ingested probiotic and indigenous gut microbiome can lead to an increase in the instability. It remains largely unclear if and how exogenous prebiotic can improve the overall gut microbiome stability in probiotic consumption. In this study, we used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 46 publications
(43 reference statements)
1
33
0
Order By: Relevance
“…Although the role of some probiotics in improving human health has been confirmed, their safety and influence on the stability of microbial environment has attracted much attention. Some kinds of exogenous probiotics can inhabit in the intestine and affect the environment by competing with the indigenous intestinal bacteria [173]. The concerns about the safety of probiotics application are bacterial infections and resistance.…”
Section: Probiotics and Prebioticsmentioning
confidence: 99%
“…Although the role of some probiotics in improving human health has been confirmed, their safety and influence on the stability of microbial environment has attracted much attention. Some kinds of exogenous probiotics can inhabit in the intestine and affect the environment by competing with the indigenous intestinal bacteria [173]. The concerns about the safety of probiotics application are bacterial infections and resistance.…”
Section: Probiotics and Prebioticsmentioning
confidence: 99%
“…The pairing of prebiotics and probiotics is also gradually emerging in many studies. Ma et al [ 25 ] found that constant supplementation with low galactose improves the stability of the intestinal microbes. Thus, probiotics may be able to work more reliably or better in the gut if they are supported by their substrates.…”
Section: Discussionmentioning
confidence: 99%
“…Blood was collected, and serum was isolated to determine TG as a blood lipid indicator. All fecal samples from week 2 and week 4 were used for high-throughput sequencing of the V3-V4 region of the bacterial 16s rRNA gene [ 24 ], and fecal samples from week 8 were processed for deep metagenomic sequencing [ 25 ]. The experimental design is presented graphically in Figure 1 A.…”
Section: Methodsmentioning
confidence: 99%
“…Prospective cohort studies have investigated the effects of probiotics on breast cancer. Animal experiments demonstrate a growing possibility that probiotics exert systemic anti-tumor effects via stimulating the immune system, regulating gut microbiota, and promoting the survival of healthy microflora 27 , 28 . Lakritz et al 29 indicated that the probiotic Lactobacillus reuteri suppressed breast carcinogenesis and increased the sensitivity of mammary cells to apoptosis.…”
Section: Breast Microbiota and Breast Carcinogenesismentioning
confidence: 99%